KULTIVASI MIKROALGA SPIRULINA PLATENSIS DENGAN VARIASI PENCAHAYAAN MENGGUNAKAN LAMPU TL DAN MATAHARI - Muyassaroh _; Rini kartika dewi; Dwiana Anggorowati (PROSIDING SNAST, 2018)
Spirulina platensis is one kind of bluish green microalgae classified into cyanobacteria, single celled and spiral shaped. The small size of Spirulina is the opposite with to big benefit from spirulina. Spirulina contain components of proteins, carbohydrates, fats, vitamins and minerals. With high carbohydrate content, spirulina has the potential as an energy feedstock that can be converted into bioethanol. Besides that in spirulina contains polysaccharides which have antitumor and antiviral effects, α-linoleic acid (GLA) which functions in cholesterol lowering, prevention of hepatitis, ficocyanin which is useful as an prevent tumors. Considering the many benefits of spirulina, various food industry, feed, pharmaceutical and other industries, it is necessary to conduct research to develop of spirulina. The cultivation of spirulina platensis was carried out in a laboratory using Walne media, fresh water which was kept at 25 - 270C, pH 7-8 and salinity 16-21, the variable used was lighting with TL light intensity of 2730 lux with a period of lighting bright (T) and dark (G) is: 6T-18G; 12T-12G; 18T-6G; 24T-0G compared to lighting using sunlight. The purpose of this research is to determine the efficient harvest age with maximum cell density. The results showed that for the 6T-18G the highest cell density was obtained on the eighteen day, which was 100,849,2569, for 12T-12G, it was obtained on the twelve day which was 182,324.84, for 18T-6G it was produced on the twelve day which was 218,312, 1019, for 24T-0G, it was found on the seven day that is 190.127,388, whereas with sunlight on the seven day with cell density of 411,624,2038, it can be concluded that with the most efficient sunshine is seven days and the highest cell density is 411,624, 2038.